CyberKnife with Tumor Tracking: An Effective Treatment for High-Risk Surgical Patients with Stage I Non-Small Cell Lung Cancer - Collins, Sean; Chen, Viola J.; Oermann, Eric; Rabin, Jennifer; Suy, Simeng; Yu, Xia; Subramaniam, Deepa; Banovac, Filip; Anderson, Eric; Collins, Brian T.; Vahdat, Saloomeh (Frontiers in Oncology, 2012)
Published data suggests that wedge resection for stage I NSCLC results in improved overall survival compared to stereotactic body radiation therapy (SBRT). We report CyberKnife outcomes for high-risk surgical patients with biopsy-proven stage I NSCLC. PET/CT imaging was completed for staging. Three-to-five gold fiducial markers were implanted in or near tumors to serve as targeting references. Gross tumor volumes (GTVs) were contoured using lung windows; the margins were expanded by 5 mm to establish the planning treatment volume (PTV). Treatment plans were designed using hundreds of pencil beams. Doses delivered to the PTV ranged from 42-60 Gy in 3 fractions. The 30-Gy isodose contour extended at least 1cm from the GTV to eradicate microscopic disease. Treatments were delivered using the CyberKnife system with tumor tracking. Examination and PET/CT imaging occurred at 3-month follow-up intervals. Forty patients (median age 76) with a median maximum tumor diameter of 2.6 cm (range, 1.4-5.0 cm) and a mean post-bronchodilator percent predicted forced expiratory volume in 1 second (FEV1) of 57% (range, 21 - 111%) were treated. A mean dose of 50 Gy was delivered to the PTV over 3 to 13 days (median, 7 days). The 30-Gy isodose contour extended a mean 1.9 cm from the GTV. At a median 44 months (range, 12 -72 months) follow-up, the 3-year Kaplan-Meier locoregional control and overall survival estimates compare favorably with contemporary wedge resection outcomes at 91% and 75% , respectively. CyberKnife is an effective treatment approach for stage I NSCLC that is similar to wedge resection, eradicating tumors with 1 to 2 cm margins in order to preserve lung function. Prospective randomized trials comparing CyberKnife with wedge resection are necessary to confirm equivalence.